A Path Analysis of Environmental and Social Factors Affecting Feeding and Swallowing Abilities in Preschool Children - Daulas Mangunsong, Roy Romey; Sutanto, Alfiani Vivi; Sudarman, Sudarman (Poltekkes Kemenkes Surakarta, 2025)
Background: Environmental and social factors influence the feeding and swallowing abilities of preschool children. However, understanding of how these factors interact to form eating and swallowing abilities is still limited. This study assesses the influence of environmental and social factors on children's feeding and swallowing abilities using various environmental and social indicators. Methods: A cross-sectional study was conducted in Surakarta, Central Java (April–August 2025), with 81 purposively selected children. Feeding and swallowing ability was the dependent variable, while family, school, economic, social, and parenting factors served as predictors. Data were collected through interviews, observations, questionnaires, and the Dysphagia Disorder Survey, and analyzed using path analysis in Stata 13. Results: Children’s feeding and swallowing abilities were significantly associated with economic conditions and food availability (b = 2.09; 95% CI: 0.08–2.58; p = 0.037), parental support and social factors (b = 3.16; 95% CI: 0.79–3.41; p = 0.002), as well as feeding practices (b = 3.27; 95% CI: 0.82–3.27; p = 0.001). Indirectly, children’s abilities were also influenced by social factors, parental support, appropriate feeding practices, school and peer environment, and social support. Conclusion: Economic conditions, parental support, and feeding practices have a direct influence on children’s feeding and swallowing abilities. In contrast, social factors, parenting styles, educational environments, and social support exert indirect effects. The main implication for health practices is the need for integrated interventions involving family economic support, parental education, social systems, and learning environments to support the development of feeding and swallowing abilities in preschool children.